(untitled) (Kathmandu University Medical Journal, 2012)
Background Non-invasive ventilation (NIV) has become an integral tool in the management of acute and chronic respiratory failure. Studies have shown that use of NIV decreases the length of hospital stay, improves symptoms and also reduces the need for invasive mechanical ventilation in patients with respiratory failure. However, NIV is not used sufficiently in our country. Objective To find out the outcome of Non Invasive Ventilation in Respiratory failure in Nepal. Methods Retrospective analysis of data of 28 patients in between June 2010- November 2010 was done. All the patients selected had respiratory failure. Records were analysed for documentation of clinical diagnosis. Arterial blood gases were assessed prior to, after starting and after discontinuation of NIV. The outcome of NIV and the need for domiciliary oxygen was evaluated at discharge. Results Thirty four patients received NIV out of which 6 were excluded from the study due to insufficient documentation. Out of these 28 patients, 27 received bi-level and one patient received Continuous Positive Airway Pressure. Mean age of patients was 66.5 years and ranged from 42-87 years. Majority (19, 79%) were from age group 60-80 years. Most common cause for the use of bi-level ventilation was chronic obstructive pulmonary disease with type 2 respiratory failure in 19 patients (67.8%). Others included obesity hypoventilation syndrome two, acute interstitial pneumonia two, cardiogenic pulmonary oedema two, Interstitial lung disease one, bronchogenic carcinoma one, and bronchiectasis one. Arterial blood gas analysis was done on admission and 12 hours or earlier after the onset of bi-level ventilation. At the time of admission, 89.3% of the patients had type 2 respiratory failure, of which 60.6% had respiratory acidosis and 67.9% of patients had pCO2 above 60 mm Hg. Arterial blood pH prior to admission ranged from 7.19 to 7.50. Twelve hours after bi-level ventilation, only 21.3% had pH <7.35 and 42.8% had pCO2 above 60 mm Hg. Non invasive ventilation was successful in 27 patients (96.4%). All patients were advised domiciliary oxygen and all patients had respiratory follow up arranged. Conclusions COPD patients with type 2 respiratory failure were seen to benefit most with NIV. It is a very cost effective and safe method of treatment and should be used first in patients with COPD with type 2 respiratory failure. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6340 Kathmandu Univ Med J 2011;9(4):256-59